2015
DOI: 10.1007/s13277-015-3642-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA-PKcs increased anticancer drug sensitivity by suppressing DNA damage repair in osteosarcoma cell line MG63

Abstract: Many chemotherapy drugs exert anticancer effects through causing DNA damage, such as DNA topoisomerase inhibitor and platinum-containing drugs. DNA damage repair is an important mechanism of drug resistance which is responsible for metastasis and recurrence after chemotherapy. DNA-dependent protein kinase (DNA-PK) plays an important role in non-homology end joining (NHEJ) pathway. In this study, we aimed to determine whether DNA-PK catalytic subunit (DNA-PKcs) is expressed in osteosarcoma MG63 cell line and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…16 PRKDC (alias: DNA-PKC, DNA-PKcs) has been reported to regulate cell proliferation, cell cycle, and apoptosis in multiple cancers. [31][32][33] Additionally, the previous study has shown that PRKDC was related to radio-resistance in ESCC. 34 Concordantly, we confirmed the upregulation of PRKDC in ESCC cell lines and that miR-488-3p targeted PRKDC in ESCC cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…16 PRKDC (alias: DNA-PKC, DNA-PKcs) has been reported to regulate cell proliferation, cell cycle, and apoptosis in multiple cancers. [31][32][33] Additionally, the previous study has shown that PRKDC was related to radio-resistance in ESCC. 34 Concordantly, we confirmed the upregulation of PRKDC in ESCC cell lines and that miR-488-3p targeted PRKDC in ESCC cells.…”
Section: Discussionmentioning
confidence: 93%
“…A former study demonstrated that miR‐488‐3p targeted PRKDC, known as a regulator of DNA damage repair, to enhance radiosensitivity in melanoma . PRKDC (alias: DNA‐PKC, DNA‐PKcs) has been reported to regulate cell proliferation, cell cycle, and apoptosis in multiple cancers . Additionally, the previous study has shown that PRKDC was related to radio‐resistance in ESCC .…”
Section: Discussionmentioning
confidence: 99%
“…After the induction of a DSB, the Ku heterodimer [composed of polypeptides of about 70 (Ku70) and 80 kDa (Ku80)] binds DNA break ends and recruits the DNA-PKcs. DNA-PKcs induces recruitment of repair proteins to DSBs and activation of checkpoints, which leads to the formation of the DNA-PK holo-enzyme [39,40] . DNA-PK then forms a functional complex with Artemis, which provides nucleolytic processing activity required to prepare DNA ends for ligation [41] .…”
Section: Inhibition Of Dna-pkcs and Ku70/80mentioning
confidence: 99%
“…DNA-PK then forms a functional complex with Artemis, which provides nucleolytic processing activity required to prepare DNA ends for ligation [41] . Many studies showed that cells deficient in DNA-PK exhibit hypersensitivity to IR [40] . Radiosensitization has been observed with wortmannin [42] which is the first identified DNA-PK inhibitor.…”
Section: Inhibition Of Dna-pkcs and Ku70/80mentioning
confidence: 99%
“…While some studies have explored the use of DNA-PK CS inhibitors to sensitize OS cells to chemotherapy [15, 16], the role of these inhibitors in sensitizing OS cells to IR remains to be investigated. KU60648 is a recently developed potent small molecule DNA-PK CS inhibitor [17].…”
Section: Introductionmentioning
confidence: 99%